Application of the SCAI classification in a cohort of patients with cardiogenic shock. Issue 3 (11th January 2020) - Schrage, Benedikt; Dabboura, Salim; Yan, Isabell; Hilal, Rafel; Neumann, Johannes T.; Sörensen, Nils A.; Goßling, Alina; Becher, Peter Moritz; Grahn, Hanno; Wagner, Tobias; Seiffert, Moritz; Kluge, Stefan; et al.
Abstract: Background: The Society of Cardiovascular Angiography and Interventions (SCAI) have recently proposed a new classification of cardiogenic shock (CS) dividing patients into five subgroups. Objective: Aim of this study was to apply the SCAI classification to a cohort of patients presenting with CS and to evaluate its ability to predict 30‐day survival. Methods: SCAI CS subgroups were interpreted based on the recent consensus statement and then applied to N = 1, 007 consecutive patients presenting with CS or large myocardial infarction (MI) between October 2009 and October 2017. The association between SCAI classification and 30‐day all‐cause mortality was assessed by logistic regression analysis. Results: Mean age in the study cohort was 67 (±15) years, 72% were male. Mean lactate at baseline was 6.05 (±5.13) mmol/l and 51% of the patients had prior cardiac arrest. Overall survival probability was 50.6% (95% confidence interval [CI] 47.5–54.0%). In view of the SCAI classification, the survival probability was 96.4% (95% CI 93.7–99.0%) in class A, 66.1% (95% CI 50.2–87.1%) in class B, 46.1% (95% CI 40.6–52.4%) in class C, 33.1% (95% CI 26.6–41.1%) in class D, and 22.6% (95% CI 17.1–30.0%) in class E. Higher SCAI classification was significantly associated with lower 30‐day survival ( p  < .01). Conclusion: In this large clinical cohort, the SCAI classification was significantly associated with 30‐day survival. This finding supports the rationale of the SCAI CS classification and calls for a validation in a prospective trial.